Optimizing multi-tenant database architecture for efficient software as a service delivery - Sanjeev Kumar Pippal; Sumit Kumar; Ruchi Rani (Universitas Ahmad Dahlan, 2024)
A multi-tenant database (MTDB) is the backbone for any cloud app that employs a software as a service (SaaS) delivery paradigm. Every cloud-based SaaS delivery strategy relies heavily on the architecture of multitenant databases. The hardware and performance costs for quicker query execution and space savings provided by the architecture of MTDBs are implementation costs. All tenants’ data may be kept in a single table with a common schema and database format, making it the most cost-effective MTDB configuration. The arrangement becomes congested if tenants have varying storage needs. In this research, we present a space-saving architecture that improves transactional query execution while avoiding the waste of space due to different attribute needs. Extensible markup language (XML) and JavaScript object notation (JSON) compare the proposed system against the state of the art. The suggested multitenant database architecture reduces unnecessary space and improves query performance. The experimental findings show that the suggested system outperforms the state-ofthe-art extension table method.